Effect of carbon nanomaterial dimension on the functional activity and degeneration of neurons. (December 2021) - Lee, Hyojin; Kim, Seongchan; Hwang, Kyeong Seob; Lim, Nu Ri; Oh, Han Bin; Cho, Il-Joo; Kim, Jongbaeg; Kim, Ki Hun; Kim, Hong Nam
Abstract: Despite growing concerns regarding the threat of airborne nanoparticle-mediated brain degeneration, the underlying pathological mechanisms remain unclear. Carbon nanomaterials, the main components of airborne nanoparticles, have multi-dimensional structures. Therefore, the dimensional effect of carbon-based nanomaterials on the regulation of neural function in brain disorders requires additional clarification. Herein, we report the interaction between zero-to three-dimensional carbon nanostructures and the amyloid-beta protein, which can either activate or interrupt neuronal functions, depending on the dimension of the carbon nanostructures. The carbon nanomaterials induced significant cellular activation by short-term exposure, while prolonged exposure eventually caused neuronal cell death. Such dimension-dependent activation or degeneration was more evident in the higher-dimension carbon nanomaterials, as confirmed by the increases in neurotransmitter secretion and synapse-related protein levels to more than five times at 72 h of monitoring and calcium signaling in the neurons. The inclusion of amyloid-beta proteins ameliorated the cytotoxic effects of carbon nanomaterials in higher-dimensional carbon nanomaterials by regulating 333 genes. We found that the ɑ-synuclein gene is the key factor in carbon-induced abnormal neuronal function. Therefore, through biological analyses and in vitro feasibility studies, this new insight may contribute toward understanding the pathological mechanism and finding a new target for therapy in human brain pathologies.